Large Solutions of Quasilinear Elliptic System of Competitive Type: Existence and Asymptotic Behavior - Lin Wei; Zuodong Yang (International Journal of Differential Equations)
We study the existence and asymptotic behavior of positive solutions for a class of quasilinear elliptic systems in a smooth boundary via the upper and lower solutions and the localization method. The main results of the present paper are new and extend some previous results in the literature.